96 A survey of junior doctor's experiences of medical leadership and management training. (12th November 2018) - Hynes, Gareth; Tweedie, Judith; Peake, Lewis; Lees, Peter
Abstract : Introduction: Outcomes for patients are better when healthcare professionals are involved in the leadership and management decisions of caregiving organisations. Training in leadership and management should therefore be prioritised for healthcare staff in the UK. Methods: We undertook a survey of junior doctors throughout the UK to gauge junior doctors' experiences of and their attitudes towards leadership and management training. This was conducted via an anonymous online survey of direct questions and free-text options. Results: A total of 400 junior doctors responded to the survey between September and December 2017. In total over 97% of respondents thought that leadership and management training was important, however around 50% felt that their own training was inadequate to implement change at even a local level. Despite the majority (83%) having completed an audit or quality improvement project, fewer than a third (31%) thought their ideas for service improvement had been sustainably implemented. Around three quarters of respondents felt that leadership and management was emphasised at the time of their annual reviews and was valued by their seniors, but fewer than 50% felt they had their seniors' support when trying to implement change. In terms of barriers to better engagement, short rotations was among the most widely cited obstacles. Dedicated time in rotas set aside for leadership and management training and tasks was seen as desirable, along with more training delivered locally and at a grade-specific level. Conclusions: The drive to improve the perception among junior doctors of the importance of leadership and management training appears to have been successful. However, there is still some way to go until junior doctors feel that the training provided is sufficient to allow them to make meaningful contributions to the way their healthcare organisation is run both now and in the future.